College quality and earnings in the Japanese labor market - Hiroshi Ono (Stockholm School of Economics, The Economic Research Institute (EFI), 2000)
The motivations underlying the pursuit of college prestige in Japan presumes a labor market that rewards workers according to the quality of the college that they attended. Yet, studies that examine the relationship between college quality and earnings in Japan remain few and riddled with shortcomings. This paper examines the returns to college education among Japanese men. Using a 1995 cross-sectional data of Japanese workers, I find that college quality significantly improves earnings. My findings confirm that college quality plays a crucial role in shaping both incentives and earnings in the Japanese labor market. The paper also examines the so-called distinctive features of the Japanese labor market, and confirms the significant impact of tenure and firm-size on earnings, and the similarity in the earnings profiles between blue- and white-collar workers.
Keywords: I21; J24; J31; N35; 330; human capital formation; returns to education